Mens : verhaal van een wonde. (Leuven : Davidsfonds, 2006)
Abdul, Lida ; Beuys, Joseph ; Bratkov, Sergey ; Chafes, Rui ; Corillon, Patrick ; Delathouwer, Fabien ; Delvoye, Wim ; Dijkstra, Anno ; Echavarria, Juan Manuel ; Galindo, Regina ; Garabedian, Mekhitar ; Ingridmwangiroberthutter ; Isaacs, John ; Lemke, André Philip ; Mamedov, Raoef ; Mozard, Tova ; Mueck, Ron ; Nauman, Bruce ; Nollet, Lien ; Pane, Gina ; Saarto, Ari ; Schwarzkogler, Rudolf ; Sedira, Zineb ; Templeton, Ed ; Weinberger, Lois & Franziska ; West, Franz ; Wildi, Ingrid
Mens, Verhaal van een wonde, CRKC (Centrum voor Religieuze Kunst en Cultuur vzw), Leuven, 16.09.2006 - 19.11.2006. Leuven Binnenstad & Abdij van 't Park Heverlee
kunstcatalogus